Boyhood among the woolies : growing up on a Basque sheep ranch - Etulain, Richard W. (Basalt Books, 2023)
"A sheepherder's son delivers a rare look at life on an early eastern Washington sheep ranch, recounting endless chores, lambing season, sheep shearing, family life, Basque history, and more"--